E-learning - Deepa, F. and Muthaiyan, R. (New Delhi A.P.H. Publishing Corporation, 2015)
Study conducted among the children have interest in mathematics and also about the multimedia especially e-learning in mathematics at high school level prescribed by Board of Secondary Education, Government of Tamil Nadu, India.
Include Illustrations and Appendix
Keywords: Mathematics--Computer-assisted instruction -- India--Tamil Nadu -- Internet in education